Coronavirus: Older Persons With Cancer in Italy in the COVID-19 Pandemic - Fratino, Lucia; Procopio, Giuseppe; Di Maio, Massimo; Cinieri, Saverio; Leo, Silvana; Beretta, Giordano (Frontiers in Oncology, 2020)
Italy is the European country firstly and hardly hit by the COVID-19 epidemic. Since February 2020, the outbreak of the epidemic in Italy with potential fatal outcomes in up to 10% of cases, urged to implement extraordinary measures to avoid a breakdown of the universal Italian national health system. The update of April 1, 2020 in Italy recorded 102,669 COVID-19 confirmed cases, median age 63 years. The deceased patients were older people (median age 80 years) and most often had a cancer diagnosis (about 20%). Thus, in the Italian extraordinary epidemiological scenario of the COVID-19 pandemic, older persons in cancer treatment are at particularly high risk of being severely affected by COVID-19. These people face a health- and economic-related emergency, which carries cultural and ethical implications as well. In accordance with the measures adopted by the Italian government to limit viral transmission, several associations of Italian oncologists have taken actions to update Elderly Cancer Care programs. In view of the new emerging needs, we herein outline practical suggestions aimed to guarantee the most adequate continuity to elderly cancer patients.